Antioxidant Properties, Phytochemical Screening of Posidonia oceanica in Sabratha Beach, Libya - Errayes, Asma; Moftah Darwish,; Ibrahim, Najat; Alshibani, Ghazala (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigates the antioxidant qualities of Posidonia oceanica, a type of seagrass that is widespread in the Mediterranean Sea, especially near Libya's Sabratha coast. Analyzing P. oceanica's phytochemicals related to any health advantages is the main goal of this study. A considerable amount of phenolic chemicals, particularly flavonoids, which are recognized for their antioxidant properties, were found by phytochemical screening. The extracts showed a great potential to reduce oxidative stress by demonstrating a notable capacity to scavenge free radicals. The importance of Posidonia oceanica as a source of bioactive antioxidant properties is highlighted in this study, which also suggests possible uses in the nutraceutical and pharmaceutical sectors.